CD56 and Tim-3 molecule expression in different monocyte subsets in physiological pregnancy - E. G. Orlova; O. A. Loginova (Медицинская иммунология)
Monocytes play an important role in the systemic immune defense against pathogens and maintaining physiological pregnancy. During pregnancy peripheral monocytes migrate into the decidua and form the pool of decidual macrophages which participate in the formation and development of placental tissues. The population of peripheral blood monocytes is phenotypically and functionally heterogeneous. In humans, there are different monocyte subsets depending on the expression of CD14 and CD16. CD56-positive monocytes are found in healthy women. Their number is positively correlated with body mass index, body fat. Tim-3 (T cell Ig and mucin domain-containing protein 3) expression is observed in peripheral monocytes during pregnancy. It is known that peripheral monocyte functions effectively change at pregnancy to form the immune tolerance at the maternal-fetal interface and the systemic immune defense against pathogens. However, the monocyte phenotype shift during pregnancy remain poorly understood. Therefore, the aim of the study was to evaluate the CD56 and Tim-3 expressions in monocyte subsets in human pregnancy. Peripheral blood mononuclear cells were isolated from peripheral blood of pregnant women (gestational age 29 weeks (28-31) by density gradient centrifugation and analyzed by flow cytometry. Peripheral blood of healthy non-pregnant fertile women (in follicular phase of the menstrual cycle) aged 21-29 years was studied as control. Pregnant women had a lower percentage of classical CD14hi/CD16- monocytes in comparison with non-pregnant. The percentages of intermediate (CD14hi/CD16+) and non-classical (CD14low/CD16+) monocytes did not change. The CD56 molecule expression was observed in all monocyte subsets in pregnant and non-pregnant women. Pregnant women had a higher percentage of CD56-positive classical (CD14hiCD16-) and non-classical (CD14lowCD16+) monocytes than non-pregnant. The percentage of CD56-positive intermediate (CD14hiCD16+) monocytes did not change. The percentages of double-positive CD56+Tim-3+ classical (CD14hiCD16-) and non-classical (CD14lowCD16+) monocytes were increased in pregnant women. The numbers of double-positive CD56+Tim-3+intermediate (CD14hiCD16+) monocytes did not change. Thus, the CD56 and Tim-3 expressions in different monocyte subsets were changed in human pregnancy.